ROLE OF HIGH-TEMPERATURE PROTEIN G IN THE VIRULENCE AND DEVELOPMENT OF ANTIMICROBIAL RESISTANCE IN SOME ORAL BACTERIAL ISOLATES (Applied Biological Research, 2024)
A marked increase in antimicrobial resistance among common bacterial  pathogens has made the search for new therapeutic targets highly imperative.  The present study was aimed to analyse the potential of bacterial chaperone  high-temperature protein G (HtpG) as a therapeutic target by determining its  role in virulence and antibiotic resistance. Two bacterial isolates obtained from  the oral cavity of healthy human subjects were characterized and tentatively identified as Staphylococcus aureus and Streptococcus mutans. Survival assays of  these isolates showed induction of thermotolerance with around 24% increase in  survival at lethal temperature after preconditioning. Protein profile studies  revealed prominent expression of proteins of 99, 77 and 40 kDa in thermo tolerance group as compared to the control. HtpG inhibition was achieved by  using a pharmacological inhibitor of human Hsp90, geldanamycin (GA). In disc  diffusion assays, there was no significant inhibitory impact of HtpG on antibiotic  susceptibility to six antimicrobial compounds in both the isolates as compared  to the control. An 18-19% reduction in biofilm-forming capacity was observed  for both isolates after GA treatment. This study lays strong experimental  evidence to the involvement of HtpG in the development of anti-microbial  resistance through biofilm formation.
Keywords: Antibiotic susceptibility; biofilm; geldanamycin; HtpG; oral isolates; thermotolerance